Workshop Dan Pendampingan Hukum Dalam Upaya Preventif Terhadap Tindak Pidana Kekerasan Seksual Di Negeri Haria - Imanuel J. A. Lawalata; Deotrich S. Sahetapy (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Existing provisions regarding sexual violence—previously scattered across various sectoral laws—have proven inadequate in preventing, protecting against, and eradicating such violence. This community service initiative in Negeri Haria was undertaken in response to the alarming prevalence of sexual violence in the area. We proposed the formation of a task force comprising the implementation team, partner representatives, and the Saparua District police. Additionally, we established a "partner village" (negeri binaan) relationship between the implementation team—operating under the Law Study Program—and the target community of Negeri Haria. The solutions we offered aim to prevent sexual violence against both adult women and children.